Expanding the citrullinome of synovial fibrinogen from rheumatoid arthritis patients - Sharma, Mandvi; Damgaard, Dres; Senolt, Ladislav; Svensson, Birte; Bay-Jensen, Anne-Christine; Nielsen, Claus Henrik; Hägglund, Per (Journal of proteomics, 2019)
Citrullination is a post-translational protein modification, which is associated with inflammation in general and is thought to play an important pathogenic role in rheumatoid arthritis (RA). Here a mass spectrometry-based proteomics approach was applied to identify citrullination sites in synovial fluid fibrinogen from four RA patients. In general, high disease activity correlated with increased number of identified citrullination sites and higher relative citrulline occupancy. Altogether, 23 sites were identified, of which 9 have not been previously reported to be citrullinated in vivo. Citrullination at site α84, α123, α129, α547, α573, α591, β334 and γ134 was identified in more than one patient, and these positions were therefore regarded as hotspots. Following citrullination of fibrinogen in vitro using human recombinant peptidylarginine deiminase 2 (PAD2), a total of 46 citrullination sites were identified, including 6 hitherto unreported in vitro citrullination sites. Twenty-two out of the 23 citrullination sites identified in vivo were also detected in vitro, supporting the validity of the identifications. SIGNIFICANCE: This work provides information about previously uncharacterized citrullination sites in synovial fluid fibrinogen from rheumatoid arthritis patients. Detection of these novel citrullination sites may prove to have diagnostic or prognostic value in RA and enhance our understanding of the immune pathogenesis.
Keywords: Male; fibrinogen; peptidylarginindeiminasa typu 2; lidé středního věku; Proteomics; citrulin; revmatoidní artritida; Mass spectrometry; proteomika; Post-translational modifications; Humans; Citrulline; Synovial fluid; posttranslační úpravy proteinů; Middle Aged; senioři; mužské pohlaví; Female; Fibrinogen; Aged; Peptidylarginine deiminase; Rheumatoid arthritis; ženské pohlaví; Protein Processing, Post-Translational; Protein-Arginine Deiminase Type 2; Citrullination; synoviální membrána; lidé; Synovial Membrane; Arthritis, Rheumatoid